A study on the accuracy and efficiency of the improved numerical model for stent implantation using clinical data. (August 2021) - Djukic, Tijana; Saveljic, Igor; Pelosi, Gualtiero; Parodi, Oberdan; Filipovic, Nenad
Highlights: numerical simulation of stent implantation within patient-specific coronary artery. arterial wall is modelled as a nonlinear, hyperelastic material. analysis of change of hemodynamic parameters before and after stent implantation. accuracy demonstrated through validation against follow up clinical data. Abstract: Background and objectives: Stent implantation procedure should be carefully planned and adapted to the particular patient in order to minimize possible complications. Numerical simulations can provide useful quantitative data about the state of the artery after the implantation, as well as information about the benefits of the intervention from the hemodynamical point of view. Methods: In this paper, a numerical model for stent implantation is presented. This numerical model simulates the stent expansion, the interaction of the stent with arterial wall and the deformation of the arterial wall under the influence of the stent. FE method was used to perform CFD simulations and the effects of stenting were analyzed by comparing the hemodynamic parameters before and after stent implantation. Results: Clinical data for overall 34 patients was used for the simulations, and for 9 of them data from follow up examinations was used to validate the results of simulations of stent implantation. Conclusions: The good agreement of results (less than 4.1% of SD error for all the 9 validation cases) demonstrated the accuracy of the presented numerical model. The developed approach can be a valuable tool for the improvement of pre-operative planning and patient-specific treatment optimization.